New neural transfer functions - Duch, Włodzislaw; Jankowski, Norbert (Zielona Góra: Uniwersytet Zielonogórski)
The choice of transfer functions in neural networks is of crucial importance to their performance. Although sigmoidal transfer functions are the most common, there is no a-priori reason why they should be optimal in all cases. In this article, advantages of various neural transfer functions are discussed and several new types of functions are introduced.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka